PA12-2-2323 Associations between firearm laws and firearm homicides in US cities: a bayesian space-time analysis. (November 2018) - Morrison, Christopher N; Kaufman, Elinore J; Humphreys, David K; Wiebe, Douglas J
Abstract : Background: Firearms caused 12 979 homicide deaths in the United States in 2015. Firearm homicides are concentrated in cities, and more firearm control laws are associated with fewer firearm homicides. However, studies examining firearm laws are typically conducted using large spatial units (e.g. states) and may fail to detect important city-level differences. Objective: The purpose of this study is to assess the effects of firearm control laws on the per capita incidence of firearm homicide in US cities. We hypothesized that cities with more laws would have fewer firearm homicides, and that the configuration of laws would affect relationships. Methods: Space-time units were 72 cities over 15 years (2000–2014). Cities were defined as US Department of Transportation metropolitan areas. The total population was 198 million in 2014 (62% of the national population). CDC Compressed Mortality Data provided counts of firearm homicides. The Boston University State Firearm Law Database provided data for laws within states per year. We calculated total counts of laws and the proportion of laws within categories of law types (e.g. background check laws, assault weapons laws). Bayesian conditional autoregressive Poisson models related laws to firearm deaths, while accounting for city demographic composition. Findings: An increase of 10 firearm control laws was associated with 3.6% fewer firearm homicides overall (IRR [Incidence rate ratio]=0.96; 95% CI:0.93–0.99). Bans on assault weapons and large-capacity magazines (IRR=0.57; 95% CI:0.48–0.66) and the absence of laws to prevent local governments from regulating firearms (IRR=0.64; 95% CI:0.60–0.70) contributed most substantially to the observed relationships. Conclusion: More firearm control laws are associated with fewer firearm homicides in US cities. Banning assault weapons and large-capacity magazines, and allowing cities to enact local laws had the greatest benefit. Policy implications: Regulators seeking to reduce the incidence of urban firearm homicide should consider additional firearm control laws.